PENINGKATAN MOTIVASI BELAJAR SISWA MELALUI PEMBELAJARAN STEM PADA MATA PELAJARAN MATEMATIKA MENGGUNAKAN RANCANGAN UNDERSTANDING BY DESIGN (UbD) DI KELAS V SEKOLAH DASAR - Annisa Dwi Yuniar; Yunita Sari; Nuhyal Ulia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to increase students' learning motivation in Mathematics subjects with STEM learning using Understanding by Design (UbD) design. This research is a collaborative classroom action research with a qualitative descriptive approach consisting of 2 cycles, namely cycle 1 and cycle 2. The data source in this study is fifth grade students of SD Negeri Lamper Lor Semarang City, totaling 25 students in the 2024/2025 school year. Data collection techniques using observation. The results of this class action research showed that there was an increase from cycle 1 to cycle 2. Cycle 1 obtained a result of 85% in the good category, while cycle 2 obtained a result of 98% in the very good category. Thus, STEM learning can increase the learning motivation of students in the fifth grade of SD Negeri Lamper Lor Semarang City.